Effects of bee propolis supplementation on neutrophils count following prolonged running - Aziz, Nurazila Idayu Abdul (Universiti Sains Malaysia, 2016)
The effect of nutritional supplementation for improving immune system have been investigated. However, to date, little is known about the effectiveness of bee propolis supplementation on immune system in male recreational runners. To investigate the effects of bee propolis supplementation on neutrophils count and selected physiological parameters (oxygen uptake and heart rate) following prolonged running in male recreational runners. Eleven healthy male participants (Age: 21.0±1.5 years; BMI: 22.3±2.5 7 ... . . . . . kg.m'") were recruited in this study. Participants performed 3 preliminary tests which include a submaximal test, a maximum oxygen uptake (VO2max) test and a familiarisation test. After that, participants performed the first exercise trial (90 min running at 60% VO2max) after an overnight fast. This was followed by 4 weeks consumption of bee propolis where they had to consume 2 tablets per day (500 mg of bee propolis per tablet). After the 4 weeks of consumption period, participants performed the second exercise trial which was carried out as similar as to the first exercise trial. During each trial, blood samples were collected pre-, during, post-, and 1 h post-exercise. In addition, oxygen uptake (VO2) and heart rate (HR) were measured pre-, during, and post-exercise. This study discovered that neutrophils count was significantly increased during exercise in both trials. However, neutrophils count was not significantly different between both trials. Likewise, the V02 and heart rate (HR) of the participants were not significantly different between both trials. As a conclusion, there were no significant effect of bee propolis supplementation on the neutrophils count, VO? and HR following prolonged exercise in male recreational runners.